Proceso de atención de enfermería a un paciente con abdomen agudo de 25 años. - Cervantes Carriel, Virginia Erika (2019)
The present clinical case is of a 25-year-old female patient who is admitted to the Guasmo Sur General Hospital with a clinical picture of 40 hours of evolution characterized by hypogastric pain that later radiates to the iliac fossa, accompanied by nausea, vomiting , thermal rise. At the time of admission, he reported pain at the level of the right iliac fossa of moderate intensity, thermal rise of 40 ° C. She has no personal pathological history, she is allergic to diclofenac, an allergic history does not refer, and a cesarean is surgical, the nursing diagnosis is identified with acute pain manifested by verbal expression, facies of pain. A nursing care plan was carried out in the pre-operative, and post-operative, prioritizing nursing interventions to expedite the speedy recovery of the patient. Favorable results were obtained during his hospital stay where the patient is assessed and discharged in good clinical conditions.